HUBUNGAN SELF COMPASSION DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK PADA MASA PANDEMI COVID-19 DI RSUD KOTA CILEGON - Ega Rakha Alvita Deli (2022)
Chronic kidney disease (CKD) is a chronic disease that accompanies a lifetime and requires long-term treatment through hemodialysis unless a kidney transplant is performed, causing a decrease in the quality of life of the sufferer. To determine the relationship between individual characteristics, and self compassion with the quality of life of CKD patients especially during Covid-19 pandemic at the Cilegon Hospital in 2022. This study used a cross-sectional study design with 35 patients with chronic kidney disease undergoing hemodialysis selected using total sampling conducted from April to Mei. 2022. Data analysis using chi-square test. Chronic kidney disease undergoing hemodialysis patients who had a good quality of life was 60,0%. There is a significant relationship between gender Pvalue : 0,015, education Pvalue : 0,041, length of hemodialysis Pvalue : 0,000, and self compassion Pvalue : 0,000 with quality of life of chronic kidney disease undergoing hemodialysis patients. Meanwhile, gender status did not have a significant relationship with the quality of life of people with chronic kidney disease undergoing hemodialysis. Gender, education, length of hemodialysis and self are related to the quality of life of chronic kidney disease undergoing hemodialysis patients. Keyword: Self-Compassion, Quality of Life, Chronic Kidney Disease, Covid-19